FAKTOR-FAKTOR YANG MEMPENGARUHI KECEMASAN IBU HAMIL TRIMESTER III - Nurfaizah Alza; Ismarwati Ismarwati (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: The purpose of this study was to determine the factors that influence on anxiety of pregnancy third trimester. This research is a descriptive cross-sectional design. The sampling technique used is consecutive sampling with the total sample 61 respondents. The analysis used is independent t test. The results showed the factors that influence on anxiety of pregnancy third trimester is the support of husband with a p value of 0,048 (p <0.05), while the age of mother, education level, occupation, gravidity and physical exercise can not be influence related to anxiety of pregnancy third trimester with p> 0,05. Conclusions factors that influence anxiety third trimester pregnant women isthe support of husband. Keywords: anxiety, pregnancy, third trimester